Tinjauan Hukum Islam Dan Hukum Positif Tentang Penyelesaian Pembiayaan Bermasalah Melalui Proses Agunan Yang Diambil Alih (AYDA) Pada Bank Syariah - RIZKI AMALIYAH (Jurnal Akuntansi dan Bisnis Syariah, 2025)
The purpose of this study is to determine whether Islamic law and positive law regulate the Foreclosed Collateral (AYDA) process in the settlement of non-performing financing in Islamic banks. This research uses literature review or library research with descriptive analysis. The steps include defining the subject, finding relevant sources, and drawing conclusions. According to research findings, Islamic bank financing is also equipped with positive legal material guarantees (based on Indonesian civil law). If the agreement made by Islamic banking is based on Islamic law and the principles of sharia contract law, this will certainly facilitate the settlement of defaults, where the bank can take over the guarantee in order to resolve non-performing financing. The bank has the right to sell the collateral by selling it itself (underhand sales), execution through direct auction (parate execution) or flat execution through the religious court if the collectability is stuck.